Development of ovum pickup and in vitro embryo production to assess fertility responses for mineral intervention studies - Black, David H. (2018)
As nutrition is of central importance to cattle fertility, this study sought to assess how veterinarians and nutritional advisers manage trace element imbalance in the UK; diagnosis and treatment. The study also sought to develop a robust system for oocyte recovery (ovum pick-up (OPU)) and in vitro embryo production (IVP) for commercial use, and to identify key factors influencing success, including oestrus synchrony and ovarian stimulation prior to OPU. The intention originally was to use OPU/IVP to investigate the impact of mineral imbalances on bovine oocyte quality, early embryo development and pregnancy establishment following embryo transfer (ET).